BLENDED LEARNING: SOLUSI MODEL PEMBELAJARAN DIMASA PANDEMI COVID-19 - Qotrunnada, Alisa; Khasanah, Nur (Indonesian Journal of Islamic Elementary Education, 2021)
Education in Indonesia is currently experiencing obstacles caused by the COVID-19 pandemic. This obstacle is not only felt by teachers, but also students and parents of students. This makes significant changes to the learning system used. In this context, Blended learning is the most significant development of a learning model during a pandemic like now. Blended learning can be defined as a mixture of online learning models and offline learning models. The purpose of this study is to describe the implementation of the blended learning learning model during the COVID-19 pandemic and analyze the supporting factors and inhibiting factors of the implementation of the blended learning learning model during the COVID-19 pandemic. The method in this study uses qualitative research. The process of data collection is done by using interviews, observation and documentation. In the implementation of the blended learning model, it gives good results because it is able to make learning more varied and not monotonous so that it is liked by many students. Although in this case there are still many obstacles that are passed during learning, the teacher can overcome them little by little well. Factors supporting the implementation of the blended learning model include the Government, Teachers, Technology. While the inhibiting factors for the implementation of the blended learning model include time, connections/networks, teachers and students. With these results, it is hoped that schools or other educational institutions can further study the concept of blended learning and implement blended learning.